95.9k views
5 votes
1.4(3x+0.5)= 1 3 (6x+2.7)

User Rfarias
by
5.3k points

2 Answers

3 votes

Corrected Question

Solve for x in the expression
1.4(3x+0.5)=(1)/(3)(6x+2.7)

Answer:


x=(1)/(11)

Explanation:

Given the expression:
1.4(3x+0.5)=(1)/(3)(6x+2.7)

Step 1: Distribute the terms


1.4(3x+0.5)=(1)/(3)(6x+2.7)\\1.4*3x+1.4*0.5=(1)/(3)*6x+(1)/(3)*2.7\\4.2x+0.7=2x+0.9

Step 2: Collect like terms


4.2x+0.7=2x+0.9\\4.2x-2x=0.9-0.7\\2.2x=0.2\\$Divide booth sides by 2.2\\x=(1)/(11)

Hope this helped?

User Williamsandonz
by
4.8k points
0 votes

Answer:

X = -0.485

Explanation:

Based on the expression, making X the subject matter.

1.4(3x+0.5)= 1 3 (6x+2.7)

Open up the bracket

4.2x + 0.7 = 78x +35.1

Collecting of like terms

4.2x -78x = 35.1+ 0.7

-73.8x = 35.8

Making x the subject

X = 35.8/-73.8

X = -0.48509

User Rlcrews
by
4.7k points